Tolerance of Clostridium perfringens biofilms to disinfectants commonly used in the food industry. (April 2017) - Charlebois, Audrey; Jacques, Mario; Boulianne, Martine; Archambault, Marie
Abstract: Clostridium perfringens is an opportunistic pathogen that can cause food poisoning in humans and various enterotoxemia in animal species. Recently, it was shown to form mono-species biofilms, a structured community of bacterial cells enclosed in a self-produced extracellular matrix. Biofilms have been associated with tolerance to antibiotics, disinfectants, and physical and environmental stresses. Very little is known about the tolerance of C. perfringens biofilm toward disinfectants. In the present study, susceptibilities of C. perfringens biofilms to five types of commonly used disinfectants on farms and in food processing environments were analysed. In this paper, we show that C. perfringens mono-species biofilms can protect the bacterial cells from the action of potassium monopersulfate, quaternary ammonium chloride, hydrogen peroxide and glutaraldehyde solutions. However, sodium hypochlorite solution was shown to be effective on C. perfringens biofilms. Our investigation of dual-species biofilms of C. perfringens with the addition of Staphylococcus aureus or Escherichia coli demonstrated that overall, the mono-species biofilm of C. perfringens was more tolerant to all disinfectants than the dual-species biofilms. For the anaerobic grown biofilms, the mono-species biofilm of C. perfringens was more tolerant to sodium hypochlorite and quaternary ammonium chloride than the dual-species biofilms of C. perfringens with S. aureus or E. coli . This study demonstrates that C. perfringens biofilm is an effective protection mechanism to disinfectants commonly used on farms and in food processing environments. Highlights: Clostridium perfringens has been shown to form mono-species biofilms. C. perfringens mono-species biofilms were able to protect the bacterial cells from the action of commonly used disinfectants. Sodium hypochlorite solution was shown to be effective on C. perfringens biofilms. Mono-species biofilms were more tolerant to disinfectants than the mixed biofilms.